Morphologic and Functional Imaging of Non-Colorectal Liver Metastases - Heusch, Philipp (Viszeralmedizin, 2015)
Liver metastases are the most frequent malignant liver lesions. Besides colorectal carcinoma, gastric carcinoma, pancreatic carcinoma, breast cancer, lung cancer, and neuroendocrine tumors are the most common entities that metastasize to the liver. The morphology of these metastases depends on the primary tumor. For morphologic and functional imaging of non-colorectal liver metastases, multiple imaging techniques such as ultrasonography, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography coupled with CT or MRI are available. This review summarizes morphologic and functional characteristics of different non-colorectal liver metastases.